Risk Perception: Chemical Stimuli in Predator Detection and Feeding Behaviour of the Invasive Round Goby Neogobius melanostomus - Szydłowska, Natalia Z; Franta, Pavel; Let, Marek; Mikšovská, Vendula; Buřič, Miloš; Drozd, Bořek (Biology, 2024)
The round goby Neogobius melanostomus is a notoriously invasive fish originating from the Ponto-Caspian region that in recent decades has successfully spread across the globe. One of its primary impacts is direct predation; in addition, when entering new ecosystems, the round goby is likely to become a food resource for many higher native predators. However, little is known either about the indirect effects of predators on the round goby as prey or its feeding behaviour and activity. The non-consumptive effect of the presence of higher native predators presumably plays an important role in mitigating the impact of non-native round gobies as mesopredators on benthic invertebrate communities, especially when both higher- and mesopredators occupy the same habitat. We tested the food consumption probability and gut evacuation rates in round gobies in response to chemical signals from a higher predator, the European eel Anguilla anguilla. Gobies were placed individually in experimental arenas equipped with shelters and exposed to water from a tank in which (a) the higher predator had actively preyed on a heterospecific prey, earthworms Lumbricus sp. (the heterospecific treatment; HS); (b) the higher predator had fed on round gobies (the conspecific treatment; CS); or (c) the water was provided as a control treatment (C). To ensure exposure to the chemical stimuli, this study incorporated the application of skin extracts containing damaged-released alarm cues from the CS treatment; distilled water was used for the remaining treatments. No significant differences were observed in either the food consumption probability or gut evacuation rate in the tested treatments. Despite the lack of reaction to the chemical stimuli, round gobies did exhibit high evacuation rates (R = 0.2323 ± 0.011 h-1; mean ± SE) in which complete gut clearance occurred within 16 h regardless of the applied treatment. This rapid food processing suggests high efficiency and great pressure on resources regardless of the presence or not of a higher predator. These findings hint at the boldness of round gobies, which did not exhibit any pronounced threat sensitivity. This would seem to suggest great efficiency in food processing and a potential competitive advantage over local native species when colonising new ecosystems, irrespective of the presence of native predators. Our study did not detect any non-consumptive effect attributable to the higher predator, given that the feeding activity of the invasive round goby was not altered.
Keywords: shreckstoff; non-native species; gut evacuation rate; food consumption; alarm cues; predation efficiency; aquatic invasions